Special issue the discourse of judging - Sarat, Austin (Bingley, U.K. : Emerald, 2012)
This special issue of Studies in Law, Politics, and Society focuses on the discourse of judging and the "language of judging" within many diverse legal scenarios. The volume features chapters specifically on: the "language of rights" within the context of abortion and same-sex marriage cases; discourses within the European Court of Justice; the modern-day place of politics in the US Supreme Court; and discussions on the two-court crisis which lead to the US Constitutional Convention of 1849. The chapters question the complex and conflicting relationship between politics and the law, understanding judicial independence, and offer an analysis of how the literary narrative of law plays a significant part in the delivery of legal judgement.
Judging without rights : public reason and the counter-majoritarian difficulty / Sonu Bedi -- On politics and law : recovering the Pritchett Synthesis / John Brigham -- "Don't they understand judicial independence?" : discourses of judging in undergraduate legal studies classrooms : judicial retention and same-sex marriage rulings / Renee Ann Cramer -- Kentucky's constitutional crisis and the many meanings of judicial independence / Emily Zackin -- Nomos and form : reading a jury of her peers / Matthew Anderson -- Talking about the European court : discourses of judging in the European Union / R. Daniel Kelemen.
Print version record
Keywords: Political Science -- Political Process -- General; Political Science -- Political Freedom & Security -- Human Rights; Law & society; Politics & government; Sociological jurisprudence; Political sociology